Relations Between Component Reading Skills, Inferences, and Comprehension Performance in Community College Readers. Issue 5 (2nd July 2020) - Feller, Daniel P.; Magliano, Joseph; Sabatini, John; O'Reilly, Tenaha; Kopatich, Ryan D.
ABSTRACT: This study was conducted to understand the reading challenges of underprepared college students. A sample of the participants was enrolled in supplemental literacy programs because they were deemed not ready for reading and writing in college. Community college participants completed a series of measures that assessed foundational skills for reading, bridging and elaborative inferences processes, a comprehension measure that reflected close comprehension of a text, and a scenario-based assessment that involved problem-solving with texts. Results suggest that bridging inferences were predictive of performance on measures of close comprehension, whereas elaborative inferences were predictive of performance on the scenario-based assessment. In terms of enrollment in supplemental literacy programs, variability in foundational skills and inferencing did not differ as a function of enrollment in these programs. However, underprepared students in this sample had greater difficulty engaging in complex literacy tasks that involved the application of information when compared to better-prepared students.